A Numerical Study on Aero-Vibro Noise of a Transonic Cavity Flow - Kadi, Oliver; Maierhofer, Martin; Serbülent, Berken; Ståhlbom, Oskar (My University, 2025)
This report is part of a project course TRA270 Engineering Fluid-Structure Interactions (FSI) that numerically investigates the Aero-Vibro noise of a transonic cavity. Inspired by previous works this project sets up a numerical solution for this case study. Therefore, the scope of the investigation is limited by several factors, primarily the availability of computational resources and time to the nature of this project being a course. After understanding the fundamentals of FSI, the M219 cavity is meshed using an unstructured trimmed cell mesher with prism layer for the fluid domain. The solid domain was discretized and coupled in STAR-CCM+ using a quadrilateral mesh. The solid-fluid two-way coupled simulation was completed in STAR-CCM+, with mostly standardized solver settings for ideal coupled flows and non-elastic deformation. Sparlart-Allmaras (SA) turbulence model is used because it provides a smaller mesh with faster computing time and provides results comparable to the original report. In addition to investigating a hybrid RANS-LES method, an unsteady RANS (URANS) method was investigated. A comparison between the methods is presented where the change is observed to be substantial with a clear and decisive advantage towards the hybrid method.
Keywords: Fluid-Structure Interactions (FSI); Transonic; STAR-CCM+; Cavity flow; RANS; LES; IDDES; M219